Sea‐level rise, habitat loss, and potential extirpation of a salt marsh specialist bird in urbanized landscapes. Issue 16 (22nd July 2018) - Rosencranz, Jordan A.; Thorne, Karen M.; Buffington, Kevin J.; Takekawa, John Y.; Hechinger, Ryan F.; Stewart, Tara E.; Ambrose, Richard F.; MacDonald, Glen M.; Holmgren, Mark A.; Crooks, Jeff A.; Patton, Robert T.; Lafferty, Kevin D.
Abstract: Sea‐level rise (SLR) impacts on intertidal habitat depend on coastal topology, accretion, and constraints from surrounding development. Such habitat changes might affect species like Belding's savannah sparrows ( Passerculus sandwichensis beldingi ; BSSP), which live in high‐elevation salt marsh in the Southern California Bight. To predict how BSSP habitat might change under various SLR scenarios, we first constructed a suitability model by matching bird observations with elevation. We then mapped current BSSP breeding and foraging habitat at six estuarine sites by applying the elevation‐suitability model to digital elevation models. To estimate changes in digital elevation models under different SLR scenarios, we used a site‐specific, one‐dimensional elevation model (wetland accretion rate model of ecosystem resilience). We then applied our elevation‐suitability model to the projected digital elevation models. The resulting maps suggest that suitable breeding and foraging habitat could decline as increased inundation converts middle‐ and high‐elevation suitable habitat to mudflat and subtidal zones. As a result, the highest SLR scenario predicted that no suitable breeding or foraging habitat would remain at any site by 2100 and 2110. Removing development constraints to facilitate landward migration of high salt marsh, or redistributing dredge spoils to replace submerged habitat, might create future high salt marsh habitat, thereby reducing extirpation risk for BSSP in southern California. Abstract : To predict how Belding's Savannah Sparrow ( Passerculus sandwichensis beldingi ) habitat might change from 2010 to 2110 under low (0.44 m/100 year; top row), moderate (0.93 m/100 year; middle row), and high (1.66 m/100 year; bottom row) SLR scenarios, we first constructed a suitability model by matching bird observations with elevation. As a result, the highest SLR scenario predicted that no suitable breeding or foraging habitat would remain at any site by 2100 and 2110. Removing development constraints to facilitate landward migration of high salt marsh, or redistributing dredge spoils to replace submerged habitat might create future high salt marsh habitat, thereby reducing extirpation risk for salt marsh obligate species in southern California.